MORPHOLOGICAL ERROR ANALYSIS ON WORD CLASSES FOUND IN STUDENTS’ DESCRIPTIVE WRITING OF THE FIFTH SEMESTER ENGLISH DEPARTMENT AT NOMMENSEN HKBP UNIVERSITY (NHU) MEDAN - Sondang Manik; Poster Sagala (Institut Pendidikan Tapanuli Selatan, 2022)
The writer did a research of fifth semester English department students at Faculty of Art and Nommensen HKBP University Medan. This research entitled : Morphological Error Analysis on Word Classes Found in Students’ Descriptive Writing of The Fifth Semester English Department at Nommensen HKBP University (NHU)- Medan The writer asked the students to write a descriptive text. When they did the test, they felt confuse to write words with correct morphology. The result of the analysis was found that they knew about morphology, but they are confused to apply that. After they finished to write a descriptive text, the writer analyzed them. The writer underlined and classified the errors into four word classes on Morphological error. There are four word classes of morphological Errors, they are noun morphological errors, verb morphological errors, adjective morphological errors and adverb morphological errors . The result of the analysis, the writer concluded that there are four word classes was found by the writer, namely noun morphological errors, verb morphological errors, adjective morphological errors, and adverb morphological error. The data of morphological erors are found 154 errors. The percentage of errors in noun morphological was 52 errors i.e, 33,8%, errors of verb morphological was 91 errors or, 59,0%, errors of adjective morphological was 7 errors i.e, 4.6%, and error of adverb morphological was 4 errors i.e, 2.6%. The result of the analysis was found that the students knew about morphology but they are still confused to write words based on the correct morphology, so they made the errors. Looking at the percentage it shows verb morphological was 91 errors or 59,0%, of 154 errors, it means that verb is mostly used in a text, to express the ideas or activities .